2023
DOI: 10.3389/fpubh.2023.1191314
|View full text |Cite
|
Sign up to set email alerts
|

Variations of work engagement and psychological distress based on three working modalities during the COVID-19 pandemic

Abstract: With the onset of the COVID-19 pandemic, the rapid spread of the SARS-CoV-2 virus became a global health threat affecting people’s mental and physical health, as well as working conditions and modalities. The reorganization of the work environment also affected work engagement and psychological distress levels. This manuscript assesses how work engagement and distress vary according to gender and age across three working modalities. We used a voluntary response sampling strategy to collect data on psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Additionally, our study's findings are consistent with those of [3] research, who identified self-perceived health and vigor at work as important predictors of mental health. In contrast, the study conducted by [35] revealed divergent findings, suggesting a notable and adverse association between psychological distress and overall job engagement scores. These differences could be due to variances in the number of participants, the environment in which the study was conducted, and the characteristics of the study group.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, our study's findings are consistent with those of [3] research, who identified self-perceived health and vigor at work as important predictors of mental health. In contrast, the study conducted by [35] revealed divergent findings, suggesting a notable and adverse association between psychological distress and overall job engagement scores. These differences could be due to variances in the number of participants, the environment in which the study was conducted, and the characteristics of the study group.…”
Section: Discussionmentioning
confidence: 83%
“…Studies performed during the COVID-19 pandemic have already shown that remote work was negatively correlated with psychological distress ( 34 , 61 , 63–66 ). This may have been due to lack of support, isolation, loneliness, low control over long working hours, decreased work productivity and reduced job satisfaction ( 64 , 65 , 67 ). The participants’ gender distribution may also be an explanation, since it has already been shown that women working remotely during the pandemic were more prone to being depressed, anxious, and stressed than men in the same situation ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants’ gender distribution may also be an explanation, since it has already been shown that women working remotely during the pandemic were more prone to being depressed, anxious, and stressed than men in the same situation ( 67 ). Remote work was conceivably over-proportionately burdensome to women, given the unequal distribution of domestic work and family responsibilities dictated by gender roles ( 63 , 64 ). This issue is particularly pronounced societies that maintain a patriarchal dominance system such as that of Brazil ( 7 , 68 , 69 ), where entrenched gender norms still contribute to the reinforcement of gender roles and inequalities ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, variations exist throughout the different stages of the pandemic, particularly when preventive measures, social distancing, or isolation became commonplace among the workforce [24,25]. It has been already observed that psychological distress was significantly and negatively correlated with work engagement [26], and that work engagement moderated the direct and indirect effects of the stress related to job insatisfaction [27].…”
Section: Introductionmentioning
confidence: 99%